Occipital Nerve Blockade for the Treatment of Occipital Neuralgia-Like Acute Postcraniotomy Headache: A Retrospective Study - Shaoheng Wang; Xueye Han; Chunmei Zhao; Fang Luo (Pain Research and Management)
Objective. The therapeutic effectiveness and safety of occipital nerve blockade (ONB) on occipital neuralgia- (ON-) like acute postcraniotomy headache (ON-APCH) was evaluated. Background. Persistent occipital neuralgia is a subclassification of chronic postcraniotomy headache and has been investigated sporadically in previous publications. The long-lasting neuralgic pain significantly impairs postoperative recovery and quality of life. However, little is known regarding ON-APCH and its management. Methods. All data were retrospectively acquired from consultation records and electronic institutional medical documents. Forty-one patients, who developed drug-resistant ON-APCH after elective craniotomy and received ONB with lidocaine for diagnoses, were included in this study, all of whom were treated using dexamethasone and lidocaine. Pain intensity and ONB correlated complications and side effects were collected and analyzed at three different time points: before ONB, at 1 day after ONB, and at discharge. Results. Nineteen males and twenty-two females aged 49.6 ± 15.2 years were diagnosed with drug-resistant ON-APCH. The mean NRS was 8.0 ± 0.9 before ONB, which later significantly decreased to 2.1 ± 1.4 and 1.6 ± 0.6 at 1 day after ONB and on discharge, respectively. At 1 month after ONB, thirty patients (73%) obtained complete pain relief without medication. At 3 months after ONB, only two (5%) patients had to continue oral medications to maintain pain relief. No adverse effects or complications were observed immediately after, or within 3 months, of the nerve blockade. Conclusions. For drug-resistant ON-APCH, early occipital nerve blockade with dexamethasone and lidocaine is an effective and safe technique, which provides adequate pain relief and may prevent further development of persistent presentation of refractory ON.